2010
DOI: 10.1097/hjr.0b013e328339cc70
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial onn-3 polyunsaturated fatty acids supplementation and all-cause mortality in elderly men at high cardiovascular risk

Abstract: We observed a tendency toward reduction in all-cause mortality in the n-3 PUFA groups that, despite a low number of participants, reached borderline statistical significance. The magnitude of risk-reduction suggests that a larger trial should be considered in similar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 18 publications
2
65
0
2
Order By: Relevance
“…3,18,20,22,24 There was no evidence that ω-3 FA reduced total mortality (Figure 3; RR=0.95; 95% CI, 0.86-1.04; P=0.28) or nonvascular mortality (RR=0.97; 95% CI, 0.84-1.11; P=0.65). The heterogeneity across the individual trial results for total mortality (I 2 =52.1%; P=0.007) was significant but once again it was hard to identify specific trials that caused this.…”
Section: Total Mortality and Nonvascular Mortalitymentioning
confidence: 90%
See 3 more Smart Citations
“…3,18,20,22,24 There was no evidence that ω-3 FA reduced total mortality (Figure 3; RR=0.95; 95% CI, 0.86-1.04; P=0.28) or nonvascular mortality (RR=0.97; 95% CI, 0.84-1.11; P=0.65). The heterogeneity across the individual trial results for total mortality (I 2 =52.1%; P=0.007) was significant but once again it was hard to identify specific trials that caused this.…”
Section: Total Mortality and Nonvascular Mortalitymentioning
confidence: 90%
“…Seventeen studies done in 57 671 participants 2,3,10,[16][17][18][19][21][22][23][24][25][26][27][28][29][30] reported 5956 deaths from any cause, and 5 studies reported 723 deaths of nonvascular origin that occurred among 13 913 individuals. 3,18,20,22,24 There was no evidence that ω-3 FA reduced total mortality (Figure 3; RR=0.95; 95% CI, 0.86-1.04; P=0.28) or nonvascular mortality (RR=0.97; 95% CI, 0.84-1.11; P=0.65).…”
Section: Total Mortality and Nonvascular Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Increased consumption of omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) and the concomitant increase in n-3 LCPUFA concentrations in the circulation has been associated with a number of health benefits in humans, including prevention of preterm birth [1], primary and secondary protection against cardiovascular disease [2], and strengthened immune defences [3].…”
Section: Introductionmentioning
confidence: 99%